Perubahan Bentuk dan Makna Bahasa Arab Mesir - Lilik Rochmad Nurcholisho (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2020)
This study was written not to bring to life the ‘Āmmiyah language or colloquial language in Egyptian Arabic, nor to give the impression of wanting to defend the existence of ‘Āmmiyah as a popular variety of languages ​​compared to the official language or Fus{h{ā. This light study aims to provide an overview of the development of new vocabulary in Arabic, especially the words used in daily life for Egyptian Arabs when communicating. The development found in this paper is the semantic development in Egyptian Arabic which undergoes a shift in meaning starting from expansion, narrowing and even giving new meanings and forms that previously did not exist or were not found in classical dictionaries such as Lisa>n al_Arab and Ta>jul ‘Aru>s or modern dictionaries such as al-Waji>z and al-Wasit.